Validasi Instrumen Untuk Menilai Kegiatan Pelaksanaan Kuliah Praktikum Mahasiswa Di Laboratorium Pendidikan - Mujakir, Mujakir; Sabarni, Sabarni; Safrijal, Safrijal; Ardiansyah, M. Edo; Zainuddin, Zainuddin (Jurnal Riset Pendidikan Kimia (JRPK), 2023)
Based on the results of the analysis and evaluation of the implementation of practicum activities at the chemistry education laboratory at UIN ar-Raniry Banda Aceh, lecturers supporting the chemistry practicum course are still constrained in assessing the activity of implementing practicum lectures in the laboratory. Objective How to validate practicum instruments to assess the activities of implementing practicum lectures that are developed. This type of research includes research and development (R&D). The population in the study was students who carried out chemistry practicums in the chemistry education laboratory at UIN Ar-Raniry Banda Aceh. The sample in this study were 30 students in third semester chemistry education. Instrument validation was developed using the FGD technique through five experts from different universities. The data obtained were analyzed based on the average score for each aspect given by the validator. The validity of each aspect of the developed instrument is determined based on the average total score for all aspects. The validity is described by referring to predetermined criteria. The results of the validation show that the developed instrument obtains a score of 94,73 or is included in the valid category.